Emotional Availability Modulates Electrophysiological Correlates of Executive Functions in Preschool Children - Schneider-Hassloff, Henriette; Zwönitzer, Annabel; Künster, Anne K.; Mayer, Carmen; Ziegenhain, Ute; Kiefer, Markus (Frontiers in Human Neuroscience, 2016)
Executive functions - a set of cognitive control abilities - mediate resilience to stress and are associated with academic achievement and health throughout life. They are crucially linked to prefrontal cortex function as well as to other cortical and subcortical brain functions, which are maturing throughout childhood at different rates. Recent behavioral research suggested that children's executive functions were related to parenting quality and child attachment security, but the neural correlates of these associations are unknown. With this study we tested in 4-to-6-year old healthy children (N=27) how emotional availability (EA) of the mother-child-interaction was associated with behavioral and electrophysiological correlates of response inhibition (a core executive function) in a Go/Nogo task, using event-related potential recordings (ERPs), and with behavioral performance in a Delay of Gratification (DoG) and a Head-Toes-Knees-Shoulders task (HTKS). Our data showed that the Go/Nogo task modulated children's ERP components resembling adult electrophysiological indices of response inhibition - the N2 and P3/LPC ERPs- , but the children's N2 and P3/LPC ERPs showed longer latencies. Higher maternal autonomy-fostering behavior and greater child responsiveness were significantly associated with smaller children's N2 Go/Nogo effects at fronto-central and parietal sites and with greater Go/Nogo effects in the N2 time window at occipital sites, over and above childrens' age and intelligence. Additionally, greater maternal sensitivity and a higher dyadic EA quality of the mother-child-interaction went along with greater occipital Go/Nogo effects in the N2 time window, but this effect clearly diminished when we controlled for children's age and intelligence. Higher maternal autonomy-support was also positively associated with better HTKS performance, and higher dyadic EA quality went along with higher HTKS and DoG scores. However, no significant associations were found between EA variables and the behavioral response inhibition measures of the Go/Nogo task. Our results suggest that parenting qualities modulate the functionality of neural circuits involved in response inhibition, an important component of executive functions. This finding, thus, indicates that parent-child interactions shape the neurocognitive development underlying executive functions.